2019
DOI: 10.1074/jbc.ra118.005465
|View full text |Cite
|
Sign up to set email alerts
|

Muscle A-kinase–anchoring protein-β–bound calcineurin toggles active and repressive transcriptional complexes of myocyte enhancer factor 2D

Abstract: Edited by Roger J. ColbranMyocyte enhancer factor 2 (MEF2) transcription factors are key regulators of the development and adult phenotype of diverse tissues, including skeletal and cardiac muscles. Controlled by multiple post-translational modifications, MEF2D is an effector for the Ca 2؉ /calmodulin-dependent protein phosphatase calcineurin (CaN, PP2B, and PPP3). CaN-catalyzed dephosphorylation promotes the desumoylation and acetylation of MEF2D, increasing its transcriptional activity. Both MEF2D and CaN bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…PP2B is widely expressed in the heart and elsewhere, and is reported to complex with various AKAPs . (20) Consistent with this, AKAP5 and PP2B were co-localized by immunoprecipitation in cardiac samples, and this relationship appeared to change under ischemia and metoprolol treatment (Fig. 5A).…”
Section: Cardiac Akap5 and Pp2b Immunoprecipitated In Heart Tissuesupporting
confidence: 79%
“…PP2B is widely expressed in the heart and elsewhere, and is reported to complex with various AKAPs . (20) Consistent with this, AKAP5 and PP2B were co-localized by immunoprecipitation in cardiac samples, and this relationship appeared to change under ischemia and metoprolol treatment (Fig. 5A).…”
Section: Cardiac Akap5 and Pp2b Immunoprecipitated In Heart Tissuesupporting
confidence: 79%
“…We next asked whether MEF2A gain-of-function would, conversely, worsen RGC survival after optic nerve crush. In addition, MEF2A Ser-408 phosphorylation is a well-established mechanism for control of MEF2A activity in cells, promoting a switch between MEF2A-dependent gene activation and repression [ 13 , 27 , 28 ]. Thus, flag-tagged MEF2A wildtype and mutant proteins were expressed by AAV2 intravitreal injection of wild type mice.…”
Section: Resultsmentioning
confidence: 99%
“…Together these data support a role for MEF2A-regulated gene expression that opposes RGC survival after axon injury. We previously found that expression of the perinuclear scaffold protein muscle A-kinase anchoring protein α (mAKAPα) is required for neurotrophic factor- and cyclic-adenosine mononucleotide (cAMP)-dependent RGC neuroprotection after optic nerve crush injury, but not during RGC development [ 20 ], while MEF2 regulation in myocytes is regulated by mAKAP signalosomes [ 27 , 39 ]. The previous finding that MEF2A expression mediates survival signaling downstream of the stress-induced DLK/LZK pathway similarly places MEF2A at a central locus in the regulation of stress-induced survival signaling [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by the results showing the synergistic effects of BRIL and CnA, and the repressive effects of RCAN1, HDAC4, and the immunosuppressive drug FK506. Previous studies have provided evidence that Ca 2+ -calcineurin is a common player leading to activation of MEF2 and NFATc [48][49][50][51][52]. The roles of MEF2C and NFATc1/c2 in skeletal biology, studied in several bone cell types (osteoblast, chondrocytes, osteocytes, and osteoclasts), could in part explain the variable cellular and tissue anomalies, and phenotypes, observed in OI type V. MEF2C is a transcription factor involved in osteoblast differentiation and gene regulation, thought to be upstream of bone-specific transcription factors RUNX2 and Osterix (OSX/SP7) [53].…”
Section: Discussionmentioning
confidence: 99%